(یاقوتى حەمەوى، ژیاننامە و کتێبى (معجم البلدان - ئەمین, نەبەز مجید (Sulaimani Journal for Humanities, 2000)
The journeys and the geographical sources present precious information about the cultural aspects of the historical researches this is in addition to same related military and hints. What makes these sources seem more precious is that a great number of their authors wrote what they had witnessed and their writings were true versions of the aspects that have been described thus the value of the journeys appear to describe the humaniterian cultures in a certain society and through out a certain period,so the writings of the globe-trotters , whatever their individual directions and personal attitudes were, show to a great extent some of the cultural features of their times as well as describing the cultures of the countttries and the situations of the situations of the peoples they contacted with. Yakut Al-Hamawi presents different stories about all these aspects , further more the historical researchers make use of him for he determined most of the sites of the Islamic world whether far or small .what increases the importance of Al-hamawi and his style and method that separated him from other geographers.